Air pollution control using hibiscus cannabinus L. (kenaf) to reduce air pollutants - Leong, Mee Jiun (2019)
Release of destructive elements from mine waste associated many of environmental impacts. Uncontrolled disposal of mine wastes occurs can be associated with increase turbidity in receiving waters or with the release of significant quantities of potentially destructive elements, acidity or radioactivity. These contaminants may spread to the pedosphere, biosphere, atmosphere and hydrosphere and cause environmental effects. Bauxite leaching into water sources resulting in reduced soil fertility as well as affecting agricultural food products and aquatic life. Bauxite occupational exposure affects the health of miners, and has negative consequences on the health of surrounding communities, such as increased respiratory symptoms, contamination of drinking water, other potential health risks from ingestion of bauxite and heavy metals, including noise-induced hearing loss and mental stress. In this research, Hibiscus Cannabinus L. (Kenaf) was used for test in order to overcome the air pollution problems. According to Handbook of Kenaf Production: Fiber, Feed, and Seed Retrieved, it can be made as adsorbents, textiles, livestock feed and fibers in new and recycled plastics. A prototype was assembled by using Acrylic board in dimension of 1000*500*500mm. A control experiment was conducted where a later of bauxite was put in the bottom of the prototype and different wind speeds was applied into the system. The concentrations of the substances were detected from the direct sense monitoring kit and dust detective air sampler. In condition of wind speed level 3, the average concentration of PM10 was reduced continuously as the thickness of kenaf fiber increased. The reduction of concentration of PM10 was from 0.028mg/m3 to 0.021mg/m3, 0.014mg/m3 and 0.012mg/m3 with one layer, two layers and three layers of kenaf fiber respectively. The PM10 concentration reduction efficiency was raised as the thickness of kenaf fiber increased. The maximum reduction efficiency was 57.1% for PM10. It can conclude that the kenaf has the ability in reducing the particular matter. Furthermore, As the wind speed increased, the concentration of air pollutants increased. NH3 has the highest amount of concentration of 0.367ppm at the highest wind speed among PM10, Cl2 and NO2. This can be concluded that the bauxite sample contained high amount of ammonia as compared to the other substances. Besides that, it also can be concluded that wind helped in activated the harmful air particles to dispersed into the air or environment. In overall, Hibiscus Cannabinus L. ( Kenaf) can be applied in air filtration system or acts as air treatment in order to reduce the harmful particles that present in the environment. Its also not expensive and easy available in Malaysia.